A review of economic involvement of Chinese Muslims in Malaysia - Kassim, Salina; Hassan, Rusni; Mahmud, Mek Wok; Fatah Yasin, Raudlotul Firdaus (Springer, 2019)
While small in numbers, the Chinese Muslim community in Malaysia has its own unique role to play in the country’s economic activity. This study reviews the current state of economic involvement of the Chinese Muslim community in Malaysia with the aim of understanding the issues and challenges facing the community. In achieving this objective, the study conducts a critical review of the literature, focusing specifically on the various aspects of the community’s economic involvement. The study hopes to provide inputs to the relevant authorities and NGOs on further improving the socio-economic well-being of the Chinese Muslim community in Malaysia.